Developing a novel nodal grading system to standardize nodal classification in gastric cancer patients with limited lymph node resection - Sharvesh Raj Seeruttun (临床与病理杂志, 2026)
Objective: To develop an easy applicable novel nodal grading system to improve the standardization of nodal classification in patients with limited lymphadenectomy. Methods: We formulated a new approach of nodal classification to classify this category of patients. Log-rank test was used for univariate analysis and Cox proportional hazards model was used for univariate and multivariate analysis. We used linear trend χ2 tests, likelihood ratio χ2 test and Akaike information criterion (AIC) value to assess the homogeneity, discriminatory ability and monotonicity of gradients of the two nodal staging systems. Results: Statistical analysis supported that both the hypothesized N’ stage and hypothesized TN’M stage outperforms the present AJCC/UICC staging system. Conclusion: We developed an easy applicable and reproducible novel nodal grading system that has a greater predicting value than the current AJCC/ UICC staging system to classify gastric cancer patients with limited lymphadenectomy.